Effects of Moisture Contents and Storage Temperatures on the Physical, Chemical and Microbiological Qualities of Non-Sulfitted Dried Apricots - Nihal Güzel; Şeref Tağı; Mehmet Özkan (Journal of Agricultural Sciences)
This study was conducted to determine the changes in the physicochemical and microbiological qualities of the non-sulfited sun dried apricots (NSDAs) at three different moisture contents (MCs, 13.7, 23.5 and 27.0%) and at four different storage temperatures (4, 10, 20, and 30 °C) for 12 months in bulk and packaged samples. NSDAs were subjected to physical (moisture, water activity, pH and reflectance colour values), chemical (browning formation, β-carotene, and acidity), and microbial (counts for total aerobic mesophilic and psycrofilic bacteria, yeast and mould, xerofilic mould and yeast, osmophilic yeast, lactic acid bacteria, Enterobacteriaceae, Staphylococcus-Micrococcus spp.) analyses at one-month time intervals. Results indicated that while the fastest brown colour formation occurred in the samples containing 23.5% MC and stored at 30 °C, the browning decelerated below 10 °C. No significant change was observed in β-carotene contents of NSDAs during storage (P>0.05). After rehydration, osmophilic yeast count of NSDAs increased by 2.5 log colony-forming units (cfu/g). Significant reductions were observed in the microbial loads of the samples at 23.5 and 27.0% MCs with the decreasing water activity (P<0.05) during storage and increasing storage temperatures. However, yeast and mould counts exceeded 5.0 log cfu/g of the samples containing 27.0% MC after 2-months storage at 20 °C. Overall, we suggest that MC and storage temperature for NSDAs should be below 23.5% and 20 °C to achieve high microbial and physicochemical qualities for a year, respectively.